1995
DOI: 10.1017/s0016672300033115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population structuring of molecular and allozyme variation ofDrosophila melanogaster Adhbetween Europe, West Africa and East Africa

Abstract: Restriction enzyme molecular variation in Drosophila melanogaster Adh was compared between three natural populations from Europe, West Africa and East Africa. The frequency distribution of silent variation in the slow allele was compatible with the neutral model in all three samples. The number of haplotypes in East Africa was significantly higher than in the other two populations. The largest divergence, as measured by ^t, was between the East African population and a group made up from the West African, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Evidence for east-west structure included pairwise F ST values, Mantel test results indicating a significant correlation between genetic and geographic distance within all of sub-Saharan Africa but not within the eastern and western population groups, neighbor-joining population distance trees depicting the separation between eastern and western populations, Structure analysis of sub-Saharan populations showing a correlation between longitude and the cluster membership of populations, and AMOVA analysis indicating that considerably more variation exists between eastern and western population groupings than among populations within those groups. These findings are consistent with previous studies of inversion frequencies (Lemeunier and Aulard 1992;Aulard et al 2002) and studies of molecular variation that had found significant differentiation between one (or two) eastern and one western African population sample (e.g., Bénassi and Veuille 1995;Michalakis and Veuille 1996;Haddrill et al 2005).…”
Section: Variabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Evidence for east-west structure included pairwise F ST values, Mantel test results indicating a significant correlation between genetic and geographic distance within all of sub-Saharan Africa but not within the eastern and western population groups, neighbor-joining population distance trees depicting the separation between eastern and western populations, Structure analysis of sub-Saharan populations showing a correlation between longitude and the cluster membership of populations, and AMOVA analysis indicating that considerably more variation exists between eastern and western population groupings than among populations within those groups. These findings are consistent with previous studies of inversion frequencies (Lemeunier and Aulard 1992;Aulard et al 2002) and studies of molecular variation that had found significant differentiation between one (or two) eastern and one western African population sample (e.g., Bénassi and Veuille 1995;Michalakis and Veuille 1996;Haddrill et al 2005).…”
Section: Variabilitysupporting
confidence: 92%
“…In contrast, studies of silent variation among Adh slow haplotypes (Bénassi and Veuille 1995) and length variation in trinucleotide coding repeats (Michalakis and Veuille 1996) found substantial differentiation between an eastern (Malawi) and a western African (Ivory Coast) population. In both of these studies, the greatest divergence was found between Malawi, on the one hand, and Ivory Coast and the cosmopolitan samples on the other hand.…”
mentioning
confidence: 89%
“…More recent studies based on molecular markers have confirmed that African D. melanogaster populations are genetically differentiated (Bénassi and Veuille 1995;Michalakis and Veuille 1996;Veuille et al 1998;Baudry et al 2004). In D. simulans, Hamblin and Veuille (1999) studied two genes, vermilion (v) and Glucose-6 phosphate dehydrogenase (G6pd), in several populations from the Old and the New World.…”
mentioning
confidence: 93%
“…Invariably the frequency of Adh s is high at the equator and declines with latitude. This clinal behaviour has been found in North America and Australasia (Parkash and Shamina, 1994;Bubli et aI., 1996), Europe and Africa (David et aI., 1989;Benassi and Veuille, 1995;Bubli et aI., 1996) and most recently in Central and South America ( Van 't Land et aI., 1993;Van 't Land et aI., 1995;Van 't Land, 1997). The latter populations, for example, showed high Adh s frequencies, varying from 0.85-0.96 for Panamanian populations (latitudinal range from 7°45'N to 9°19'N) and even as high as 0.99 in Ecuador (latitude 2° 13'S), while Adh s frequencies varied clinally from 0.34-0.07 over a long North-South transect in Chile (latitudinal range from 18°28'S to 41 °30'S).…”
Section: The Adh Polymorphismmentioning
confidence: 64%